Giving voice to people: experiences during mild to moderate acute exacerbations of COPD - Machado, Ana (2022)
Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) have a negative impact on health status and disease progression, but their clinical presentation is heterogenous. A comprehensive understanding of people's experience during AECOPD is needed to develop person-centred interventions, such as pulmonary rehabilitation (PR). This study aimed to explore people's experience during mild to moderate AECOPD, and their thoughts on PR during this period.